Eastern Europe’s energy challenge: meeting its EU climate commitments - Buchan, D (Oxford Institute for Energy Studies, 2010)
This new paper calls for a new EU energy and climate deal in which east European member states would be required to do more – but also be paid more – to increase renewable energy and improve energy efficiency. David Buchan argues Brussels is right to look east for further emission reductions and that extra money can be found for the 10 new member states there by redirecting funds within the existing EU budget and by Europeanizing national renewable energy subsidies. The 76-page study traces central and eastern Europe’s considerable progress in transforming its energy system since emerging from communism 20 years ago but warns its governments that they ‘cannot be easily helped more if they will not help themselves’ by giving climate change the same priority as energy security.